2020
DOI: 10.3389/fendo.2020.00294
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Induced Changes in Bone Marrow Homeostasis

Abstract: Obesity is characterized by low-grade inflammation, which is accompanied by increased accumulation of immune cells in peripheral tissues including adipose tissue (AT), skeletal muscle, liver and pancreas, thereby impairing their primary metabolic functions in the regulation of glucose homeostasis. Obesity has also shown to have a detrimental effect on bone homeostasis by altering bone marrow and hematopoietic stem cell differentiation and thus impairing bone integrity and immune cell properties. The origin of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 199 publications
(165 reference statements)
1
40
2
1
Order By: Relevance
“…Obesity also mediates changes in bone-marrow, where immune cells are originated. This stem cell differentiation impairment affects systemic inflammatory pathways [ 38 ].…”
Section: Obesity Inflammation and Oxidative Stressmentioning
confidence: 99%
“…Obesity also mediates changes in bone-marrow, where immune cells are originated. This stem cell differentiation impairment affects systemic inflammatory pathways [ 38 ].…”
Section: Obesity Inflammation and Oxidative Stressmentioning
confidence: 99%
“…Further work is needed to reproduce these findings, considering important factors such as age and gender, and better define whether the metabolic benefits of UVR 16 are related to changes in cDC proportions in iBAT, if functional links between MEP, vascularisation and whitening of BAT exist, and how findings here in mice are relevant to human biology. While obesity is associated with changes in the cell composition of bone marrow, including HSPC 33 , little is known of its effects on stem cells in human BAT.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on obesity have demonstrated that a rise in bone marrow adiposity promotes osteoporosis and impairs several immune-associated functions [216,217]. An increase in bone marrow adiposity can have an impact on bone marrow stem cell lineage differentiation towards myelopoiesis.…”
Section: Adiposity and Cns Injurymentioning
confidence: 99%
“…SCI individuals not only experience increased adiposity in these two common regions of the body, but also a rise in bone marrow adipose tissue [ 197 ]. Recent studies on obesity have demonstrated that a rise in bone marrow adiposity promotes osteoporosis and impairs several immune-associated functions [ 216 , 217 ]. An increase in bone marrow adiposity can have an impact on bone marrow stem cell lineage differentiation towards myelopoiesis.…”
Section: Energy Balance Lipid Accumulation and Adipose Tissuementioning
confidence: 99%